Soil Fertility Assessment and Spatio-Temporal Analysis of Paddy Field Change In Gorontalo Under LP2B Policy - Yusriyah Atikah Gobel; Merita Ayu Indrianti; Aditya Djaini; Ivan Taslim (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
This study quantitatively assessed the intrinsic soil quality and spatio-temporal dynamics of paddy field conversion in Gorontalo Regency between 2017 and 2023, specifically under the Sustainable Food Agricultural Land (LP2B) policy. The fundamental inquiry of this research concerns the real efficacy of passive regulatory policy instruments in protecting agricultural natural capital against intense development pressures. Utilizing Sentinel satellite imagery and the Random Forest algorithm within the Google Earth Engine (GEE), detailed change detection and zonal analyses were performed. This was augmented by empirical field sampling and laboratory analysis to quantify the mean levels of critical soil fertility indicators, including Organic Carbon (OC) and Total Nitrogen (TN), in protected and newly established areas. A significant policy paradox was identified. While the regency experienced a net increase of 4,226.54 ha in total paddy field area, the legally protected LP2B zones suffered an undeniable net loss of 23.76 ha. Crucially, the soils lost from LP2B areas were intrinsically superior, exhibiting significantly higher mean levels of OC (3.15% vs. 1.88%) and TN (0.28% vs. 0.15%) compared to the newly established areas outside the LP2B boundary, which utilized lower-quality, marginal land. The most important findings highlight that the policy has failed to preserve the highest quality land, resulting in resource substitution (quality for quantity). This study strongly recommends the adoption of spatially targeted incentive strategies and the integration of a Weighted Land Loss Metric, based on soil fertility parameters, into policy monitoring to ensure the long-term sustainability and resilience of regional food production systems.